2019
DOI: 10.1111/tpj.14597
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging combined with machine learning as a tool to obtain high‐throughput plant salt‐stress phenotyping

Abstract: Summary The rapid selection of salinity‐tolerant crops to increase food production in salinized lands is important for sustainable agriculture. Recently, high‐throughput plant phenotyping technologies have been adopted that use plant morphological and physiological measurements in a non‐destructive manner to accelerate plant breeding processes. Here, a hyperspectral imaging (HSI) technique was implemented to monitor the plant phenotypes of 13 okra (Abelmoschus esculentus L.) genotypes after 2 and 7 days of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 45 publications
1
66
0
Order By: Relevance
“…Another way to identify subtle abiotic stress signals using spectral imaging is by correlating reflectance data with other more laborious, timeconsuming, or costly measurements correlated to the stress response. Feng et al (2019) found strong correlations between hyperspectral measurements of okra [Abelmoschus esculentus (L.) Moench] leaves with measurements linked to leaf chlorophyll content and fresh weight traditionally used to assess salt stress across crops. A common problem when analyzing spectral data of plant surfaces is taking into account uneven light scattering that occurs upon the interaction between incident light and the plant surface being captured (Makdessi et al, 2017).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to identify subtle abiotic stress signals using spectral imaging is by correlating reflectance data with other more laborious, timeconsuming, or costly measurements correlated to the stress response. Feng et al (2019) found strong correlations between hyperspectral measurements of okra [Abelmoschus esculentus (L.) Moench] leaves with measurements linked to leaf chlorophyll content and fresh weight traditionally used to assess salt stress across crops. A common problem when analyzing spectral data of plant surfaces is taking into account uneven light scattering that occurs upon the interaction between incident light and the plant surface being captured (Makdessi et al, 2017).…”
Section: Core Ideasmentioning
confidence: 99%
“…Moghimi et al (2018) circumvented plant architectural differences by identifying endmembers, or single inherent values representative of a given property, indicative of all plant pixels for a given inbred genotype in a given treatment and used these to identify salt stress across wheat lines. Feng et al (2019), on the other hand, was able to develop an instance segmentation model using deep learning to segment individual okra plant leaves for further evaluation, which is a suitable approach for crops where leaves lie relatively flat horizontally with respect to the sensor.…”
Section: Core Ideasmentioning
confidence: 99%
“…Rather than collecting spectra from an entire image or an entire plant leaf, where spectra from the stressed and unaffected areas are mixed together, hyperspectral imaging can provide more sophisticated data that can isolate spectra only from the affected area and identify specific imaging patterns and characteristics. This method has become increasingly popular for plant phenotyping and stress detection in agriculture [29][30][31] and has been used to identify plant responses to both abiotic and biotic stresses, such as drought stress in maize [32] and barley [33], yellow rust [34] and powdery mildew [35] in wheat, salt stress in okra [36], and Black Sigatoka disease in banana plants [37].…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…Milella et al [74] proposed methods for automated grapevine phenotyping. Feng et al [75] combined machine learning with hyperspectral imaging to develop a tool for salt-stress phenotyping.…”
Section: H Phenotypingmentioning
confidence: 99%